PENERAPAN AI DALAM SISTEM INFORMASI MANAJEMEN UNTUK MENINGKATKAN EFISIENSI BISNIS (APPLICATION OF AI IN MANAGEMENT INFORMATION SYSTEM TO IMPROVE BUSINESS EFFICIENCY) - Agfahmi Dinata; Muhammad Irwan Padli Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Increasing business efficiency is the main goal for every company. As technology develops, AI has emerged as a potential solution to increase efficiency in various aspects of business, including management information systems. This journal discusses the application of artificial intelligence in management information systems to improve business efficiency. It discusses how artificial intelligence can help in data processing, analysis, decision making, and automation of various business processes. Apart from that, this journal also discusses the challenges and opportunities faced in implementing artificial intelligence, as well as providing recommendations for effective implementation. It is hoped that this research can contribute to the development of smarter and more efficient management information systems, as well as help companies achieve more optimal business goals.